VD_FINDINFO AI 301/19 - 345/2019 vom 28. Oktober 2019 - VD Tribunal cantonal (2019)
ASSISTANCE JUDICIAIRE, REJET DE LA DEMANDE, LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ | 37 al. 4 LPGA, 61 LPGA, 82 LPA-VD